The Role of Social Media and Its Implication for Democracy in 2020 U.S. Elections - Andika Murdani; Halifa Haqqi; Satria Alchatib (Ilomata International Journal of Social Science, 2022)
We can see the growing use of social media for politics through 2020 U.S. elections. This social media presence has the potential to shift the perspective of democracy. This paper is a reflection to explore the use of social media in the United States democracy, especially in the 2020 election. This paper explained that social media has a significant role in the United States democracy, including those of the 2020 U.S. presidential election. Social media, with its shortcomings and advantages, contributed greatly to the election results, increasing public engagement, and increasing political participation. On the other hand, social media also gave rise to public polarization in the U.S. and opened up foreign intervention opportunities. However, by the 2020 U.S. election, the foreign intervention was relatively low, so that it did not have enough effect on the election results. Trump and Biden became two candidates who understood this social media potential and sought to attract voters in their respective ways. With the right and structured strategy, Biden was able to achieve deeper engagement through numerous interactions on social media. As the result, Biden emerged as the winner of the election, one of which with social media support.